Selection of the Transport Mode Using the AHP Method within Distribution Logistics of Motor Fuels - Hruška, Roman; Kmetík, Matej; Chocholáč, Jan (My University, 2021)
To remain competitive and respond to rapidly changing markets, we need to increase flexibility in today's global marketplace. In this respect, the selection of the appropriate mode of transport is one of the most important functions to be performed by logistics. The selection of the appropriate mode of transport is a multi-criteria problem involving both quantitative and qualitative criteria. This paper deals with the selection of the mode of transport using the Analytic Hierarchy Process method (AHP). AHP is a method of decomposing a complex un-structured situation into simpler components to create a hierarchical system problem. This paper describes a general model of selection of transport mode using AHP including its application to a manufacturing company that selects the appropriate mode of transport from three potential transport modes. The aim of this paper is to create a useful decision support tool for selection of the transport mode using the AHP method within distribution logistics of motor fuels. This tool helps companies to make the right decision on the choice of transport mode by taking into account different importance of the different criteria that influence the decision-making process.
Výběr druhu dopravy použitím metody AHP v rámci distribuční logistiky motorových paliv
Keywords: transportation; distribution logistics; AHP method; Saaty method; decision-making; transport mode; doprava; distribuční logistika; metoda AHP; rozhodování; druh dopravy